Western Balkans Regular Economic Report, No. 19, Spring 2021 : Subdued Recovery - World Bank (World Bank, Washington, DC, 2021)
In 2020 COVID-19 (coronavirus) plunged the Western Balkan countries, like the rest of the world, into deep recession. Economic activity contracted by an estimated 3.4 percent - the worst downturn on record. The primary causes were the drop in both domestic and foreign demand and disruptions in supply chains, especially early in the year when activity in a number of sectors simply shut down. Countries like Montenegro that have a services or tourism-oriented economy, and those where more stringent containment measures and lockdowns were imposed fared the worst. The economy began to reactivate in Q3 2020, supported by a partial easing of stringent lockdowns and the revival of global demand as vaccine development advanced. However, in late 2020 restrictions were renewed in response to a resurgence of infections across most of the region; they have kept the recovery subdued. The crisis has led to significant job losses and interruptions in welfare improvements, but the labor market is rebounding from the troughs of the recession. As noted in the Fall 2020 Regular Economic Report (RER), the pandemic halted a decade of progress in boosting incomes and reducing poverty: Since its start 139,000 jobs have been lost and between 165,000 and 336,000 people in theregion were pushed into poverty. However, job support schemes and other government measures limited the labor market fallout and helped to prevent steeper spikes in poverty. By yearend, the labor market had recovered half its pandemic losses, but large numbers of people are still unemployed, and many dropped out of the labor force discouraged by the poor economic prospects. Moreover, workers with less education, women, youth, those in contact-intensive sectors, and those informally employed have suffered disproportionate livelihood and income losses.